Peptidoglycan Endopeptidase Spr of Uropathogenic Escherichia coli Contributes to Kidney Infections and Competitive Fitness During Bladder Colonization - Huang, Wen-Chun; Hashimoto, Masayuki; Shih, Yu-Ling; Wu, Chia-Ching; Lee, Mei-Feng; Chen, Ya-Lei; Wu, Jiunn-Jong; Wang, Ming-Cheng; Lin, Wei-Hung; Hong, Ming-Yuan; Teng, Ching-Hao (Frontiers in Microbiology, 2020)
Uropathogenic E. coli (UPEC) is the most common pathogen of urinary tract infections (UTIs). Antibiotic therapy is the conventional measure to manage such infections. However, the rapid emergence of antibiotic resistance has reduced the efficacy of antibiotic treatment. Given that bacterial factors required for the full virulence of the pathogens are potential therapeutic targets, identifying such factors may facilitate the development of novel therapeutic strategies against UPEC UTIs. The peptidoglycan (PG) endopeptidase Spr (also named MepS) is required for PG biogenesis in E. coli. In the present study, we found that Spr deficiency attenuated the ability of UPEC to infect kidneys and induced a fitness defect during bladder colonization in a mouse model of UTI. Based on the LC/MS/MS analysis of the bacterial envelope, spr deletion changed the levels of some envelope-associated proteins, suggesting that Spr deficiency interfere with the components of the bacterial structure. Among the proteins, FliC was significantly downregulated in the spr mutant, which resulted in reduced motility. Lack of Spr might hinder the function of the flagellar transcriptional factor FlhDC to decrease FliC expression. The motility downregulation contributed to the reduced fitness in urinary tract colonization. Additionally, spr deletion compromised the ability of UPEC to evade complement-mediated attack and to resist intracellular killing of phagocytes, consequently decreasing UPEC bloodstream survival. Spr deficiency also interfered with the UPEC morphological switch from bacillary to filamentous shapes during UTI. It is known that bacterial filamentation protects UPEC from phagocytosis by phagocytes. In conclusion, Spr deficiency was shown to compromise multiple virulence properties of UPEC, leading to attenuation of the pathogen in urinary tract colonization and bloodstream survival. These findings indicate that Spr is a potential antimicrobial target for further studies attempting to develop novel strategies in managing UPEC UTIs.